?NEW MITE (Hveorus) FROM CENTRAL PUNJAB (PAKISTAN) IN THE FAMILY ACAR- IDAE (ACARI: ASTIGMATA) - Sarwar, Muhammad (Biological Sciences - PJSIR, 2000)
One new species Lackerbaueria fatigo representing the genus Lackerbaueria Zakhvatkin, 1941 is described from the hypopial stage. A key, comparison of characters, similarity matrix and phenogram are given to all the known species in this genus.